Equilibrium and dynamic interfacial properties of protein/ionic-liquid-type surfactant solutions at the decane/water interface - Cao, Chong (Langmuir : the ACS journal of surfaces and colloids, 2014)
The interfacial behavior of β-casein and lysozyme solutions has been investigated in the presence of an ionic liquid-type imidazolium surfactant ([C16mim]Br) at the decane/water interface. The dynamic dilational properties of the protein/surfactant solutions are investigated by the oscillating drop method and interfacial tension relaxation method. The interfacial tension isotherms for the mixed adsorption layers indicate that the increased addition of [C16mim]Br to a pure protein changes the properties of the complex formed at the decane/water interface. Whereas the interfacial tension data of the protein/surfactant mixed layers do not clearly show differences with changing bulk composition, the dilational rheology provides undoubted evidence that the structure and, in particular, the dynamics of the adsorbed layers depend on the bulk surfactant concentration. The experiment data for β-casein/[C16mim]Br solutions indicate that at higher bulk [C16mim]Br concentrations, β-casein in the interfacial layer is subject to conformational changes, where it gives space to [C16mim]Br molecules in the form of coadsorb rather than replacement; in contrast, in lysozyme/[C16mim]Br solutions some lysozyme molecules desorb from the interface due to the competitive adsorption of free [C16mim]Br molecules. Experimental results related to the interfacial dilational properties of the protein/surfactant solutions show that the dilational modulus turns out to be more sensitive to the conformation of protein/surfactant mixture at the liquid interface than the interfacial tension